EXPLORING THE EFFECTIVENESS OF BEHAVIORAL INTERVENTIONS ON MEALTIME BEHAVIOR OF CHILDREN WITH AUTISM SPECTRUM DISORDER: A SYSTEMATIC REVIEW - INDU PC; GOWRISHANKAR A; RIAZ KM; JIBIN KUNJAVARA; INDIRA NAIR L; JAYALATHA KT; TINTU JOSE; VIJAYARAGHAVAN R; RAHMATH K; SANGEETHA V JOICE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This systematic review assess the impact of various behavioural interventions implemented by the care givers to influence the mealtime behaviours of children with Autism spectrum disorder (ASD). It reflect the scope of teaching basic behavioural interventions to the parents which can improve the mealtime behaviours and quality of life of their children. This systematic review is aimed to explore the effectiveness of behavioural interventions on mealtime behaviour of children with Autism spectrum disorder. Methods: Preferred Reporting items for Systematic review and Meta analysis [PRISMA] guidelines were adopted to review the studies. PubMed, PubMed Central, Science Direct, Scopus, Web of Science, Oxford, Ovid, Psych Info and Delnet were searched. Result: Five experimental tudies that used Brief Mealtime Behaviour Inventory (BAMBI) to assess the mealtime behaviour of children with ASD were selected for the review. The reviews demonstrated that there was a significant difference in the mean score of mealtime behaviours among autistic children post intervention. Conclusion: The study findings emphasise that parent training inculcated with principles of behavioural therapy appears to have a significant impact on reducing eating behaviours of children with ASD.